Charcoal Properties of Malaysian Bamboo Charcoal Carbonized at 750 °C - Nurhazwani Jarawi; Ismail Jusoh (BioResources, 2023)
The carbonization of five Malaysian bamboo species, namely Bambusa vulgaris, Dendrocalamus asper, Gigantochloa hasskarliana, Gigantochloa levis, and Schizostachyum brachycladum, was conducted to investigate the charcoal properties and compare the quality of bamboo charcoal produced based on proximate analysis. Carbonization at 750 °C using a modified Iwasaki steel drum kiln was successful for all bamboo species. Bamboo morphological features varied and basic density increased with culm height. A charcoal yield of more than 30% was recorded in all bamboo species except for B. vulgaris and D. asper. Charcoals made from D. asper and G. hasskarliana could serve as the alternative raw material for charcoal production in charcoal industries due to their low moisture, low volatile matter, low ash, and high fixed carbon content. All species had a mean gross calorific value between 24.4 and 29.2 MJ/kg. Among different culm sections, the bottom section produced the best quality charcoal. The charcoal quality from all species was of acceptable quality for domestic use.